Klasifikasi Penyakit Kardiovaskular Menggunakan Metode Fuzzy K-Nearest Neighbor (FKNN) - Cahyani, Ni Komang Santi; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p16, 2022)
Cardiovascular disease is a non-communicable disease that can cause death due to interfering with heart function. In this case, the classification of cardiovascular disease does make it easier for other medical personnel to help diagnose cardiovascular disease. Cardiovascular disease classification uses the Fuzzy K-Nearest Neighbor (FKNN) method to determine the optimum value of the nearest neighbor. The classification of cardiovascular disease is divided into two, having cardiovascular disease and not having cardiovascular disease. The results of classification using the Fuzzy K-Nearest Neighbor (FKNN) method with testing using a confusion matrix resulted in an accuracy of 80.21% at values of K = 13 and K = 15.